Regional Climate Model Sensitivity to Domain Size for the Simulation of the West African Summer Monsoon Rainfall - Nana A. K. Browne; Mouhamadou B. Sylla (International Journal of Geophysics)
We use the International Centre for Theoretical Physics (ICTP) Regional Climate Model (RegCM3) to study the impact of different domain sizes on the simulation of the West African summer monsoon rainfall and circulation features. RegCM3 simulates drier conditions over the default domain (RegCM-D1) and its westward extension (RegCM-D2), much less dryness over the eastward extended domain (RegCM-D3) and excessive wetness in the domain extended northward into the extratropical regions (RegCM-D4). This overestimation is related to the existence of larger source of humidity due to the inclusion of a more significant portion of the Atlantic Ocean and to a weakening of the African Easterly Jet (AEJ), which both favor stronger westerlies advecting moisture towards the land. The best performance is, however, captured in the RegCM-D3 experiment, and this originates from a simulation of moderate westerly moisture fluxes along with a stronger AEJ and occurrences of more frequent African Easterly Waves (AEWs). Therefore, the choice of the domain for regional climate model simulation of the West African summer monsoon rainfall is of critical importance, and caution needs to be taken to account for the main regional forcings including mostly the necessary humidity sources of the tropical Atlantic Ocean and the AEWs genesis region upstream of Sudanese Highlands.